Gastric outlet obstruction associated with congenital diaphragmatic hernia - Robin Mawson; Jean Murdoch; Diane Kenwright; Mark D. Stringer (Elsevier, 2019)
We report an infant who developed complete gastric outlet obstruction secondary to gastric antral mucosal hyperplasia and muscular hypertrophy after CDH repair. This condition has been reported only once before when it also occurred in association with congenital diaphragmatic hernia. Other causes of gastric outlet obstruction in the newborn were excluded. The infant recovered well after undergoing a gastric antrectomy. The cause of this obscure condition is unknown. This rare condition needs to be considered in an infant who develops gastric outlet obstruction after CDH repair. Keywords: Gastric outlet obstruction, Gastric antrum hypertrophy, Prepyloric stenosis